HIV/AIDS awareness in schoolgoing adolescents - Dr Vinod Singh Tagore; Dr Nawal Kapoor (Pediatric Review: International Journal of Pediatric Research, 2017)
Objectives: To assess the awareness of school children regarding Human immunodeficiency virus [HIV] to devise strategies or subjects for future programmes and to provide suggestions for school HIV education.Methodology: As about 11 schools were taken in study, 7 were government schools and 4 were Private schools. 7 from the urban areas and 4 from the rural areas.In a school 40 – 50 students were surveyed. Total 489 students were divided in different age group i.e. 10-13 year, 14-16 year and 17-19 year, males and females, students were also studied in division of rural and urban group. The students were administered a pre-designed proforma, which included multiple choice questions.Results: In our study 489 students scored 65.4% in knowledge about disease, 57.5% in knowledge in complication of disease, 59.9% in knowledge about prevention of disease, 66.8% in knowledge about treatment of disease, 48.5% in knowledge about etiology of disease and 39.1% in knowledge about medico legal aspect of disease.Conclusion: The study showed tremendous lacunae in awareness of all Reproductive Health (RH) matters. There is a need for evolving information, education, and communication strategies to focus on raising awareness on RH and gender related issues. A sociocultural research is needed to find the right kind of sexual health services for young girls and boys